Una mutación en UDP-GlcNac : Dolicohol Fosfato N-acetilglucosamina-1-Fosfato transferasa (GPT) causa el fenotipo stpm365 en Danio rerio - De La Guardia Orozco, Ana Catalina (2006)
In this work we show that the zebrafish stpm365 mutation interferes with the craniofacial development by disrupting the gene that encades far the Gpt enzyme which is involved in the first critica/ step of the N-glycosylation pathway.